Shaping Dynamic Capabilities Through Merger & Acquisition Activity: Context Of Banking Industry - Aldriza Fariq; Reza Erlangga; Muhammad Hafish Zafran Ghaly (Jurnal Manajemen Indonesia, 2022)
Digitalization is being accelerated by the ongoing COVID-19 crisis, which has the boosted demand for digital services. The Banking industry must adapt to keep up with the digitalization disruption by exploiting Mergers and Acquisitions (M&A) or establishing Financial Technology related to capturing dynamic capabilities. Dynamic capabilities in the banking context can be achieved whenever additional values were shown in the post-M&A process, bringing the financial and operational performance in better condition for the acquiring banks. The purpose of this paper focuses on exploring mergers and acquisitions in the banking industry through the lens of dynamic capabilities. Hence, based on several literatures that has been elaborated, this paper aims to formulate the conceptual model of dynamic capabilities in mergers and acquisitions in the banking industry. The conceptual model demonstrates that the convergence of capability in sensing and seizing opportunities can result in new product development, while the nexus of sensing and transforming capabilities generates cost and operational efficiency in the context of the banking industry. Keywords—Dynamic capabilities; Merger & Acquisition; Banking; Conceptual Model; Financial Technology; Value creation. COVID-19.